2019
DOI: 10.9734/jenrr/2019/v2i330076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygenated Additives with Diesel on the Performance of D I Diesel Engine

Abstract: The primary objective of this work is to reduce the particulate matter (PM) or smoke emission and oxides of nitrogen (NOx emissions) the two important harmful emissions and to increase the performance of diesel engine by using oxygenated additives with diesel as blend fuel. Formulation of available diesel fuel with additives is an advantage than considering of engine modification for improvement of higher output. From the available additives, three oxygenates are selected for experimentation by considering man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this line, several studies have reported diethyl carbonate as an effective oxygenated additive in proportions of up to 20% for fossil diesel, resulting in lower soot and NOx emissions emitted by the engine, as well as an improved engine performance [25][26][27][28]. The effect DEC on the performance and emission of a diesel engine has been also analyzed on blends with waste plastic oil and diesel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, several studies have reported diethyl carbonate as an effective oxygenated additive in proportions of up to 20% for fossil diesel, resulting in lower soot and NOx emissions emitted by the engine, as well as an improved engine performance [25][26][27][28]. The effect DEC on the performance and emission of a diesel engine has been also analyzed on blends with waste plastic oil and diesel.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of diesel, sunflower oil, castor oil, and diethyl carbonate. Density and kinematic viscosity are experimentally obtained, whereas the other data are taken from the literature[27,31,32].…”
mentioning
confidence: 99%